Landing and distribution of captured fish in selected landing centers in Kishoreganj haor, Bangladesh - Nowsad, Alam AKM; Akter, Mousumi; Shahriar, Al (Asian-Australasian Journal of Bioscience and Biotechnology, 2021)
The present study illustrates species diversity, landing quality and catch composition of fish in 10 fish landing centers of 5 haor upazilas of Kishoreganj haor for 12 months from January 2018 to December 2018. A total of 15 different types of fishing gears were detected to harvest fish in different stations throughout a year. Most of the fishing (46.88%) was conducted by small groups of 2 – 5 fishers, while 24.87% of the fishing was conducted by 6 – 10 fishers. The average depth of water in haor associated rivers and inundated lands during monsoon period varied from 4.87±0.99 to 15.2±6.71 and 2.6±0.55 to 6.2±2.68 feet respectively. Fifty different types of fish species were landed in the selected 10 landing centers, where both cultured fish and captured fish were present. Fishes under the Cyprinidae family included 9 species, viz. Labeo rohita. Gebelion catla, Cirrhinus cirrhosus, Labeo calbasu, Hypophthalmichthys nobilis, Hypophthalmichthys molitrix, Cyprinus carpio, Ctenopharyngodon idella, Labeo gonius covered a maximum of 12450.61±468.32 MT. The second largest landed fish under the family Schilbeidae included 4 species Silonia silondia, Mystus armatus, Mystus cavasius Pseudeutropius atherinoides. Other fish species landed were identified as: 4 species under the family Mastacembelidae, 2 species under Siluridae, 3 species under Clupidae, 1 species under Ambassidae, 2 species under Palaemonidae, 3 species under Channidae, 1 species under Gobidae, 2 species under Bagridae and 1 species from each of the family Heteropneustidae, Pangasiidae, Clariidae, Ailiidae, Botiidae, Nandidae, Cichlidae, Anabantidae, Osphronemidae, Ambassidae, Notopteridae, Notopteridae,Belonidae and Gobiidae. Highest number 14 species landed were under catfish category, followed by 9 species of major carp. The captured total fish landed in 10 landing centers in 12 month period accounted 12,574±1029.64 MT, but the cumulative total landed fish, including pond fish, was 15,795±1666061.93 MT, as calculated by 45 Aratdars of 10 landing centers. About 88.35% fishermen sold the captured fish at local arat, but the rest (11.65%) were sold to large traders (paiker), retailers and consumers. A 56.6% of the fishermen cleaned the captured fish by river water, while 43.4% fishermen did not use water for washing fish before selling. After harvest, 45.62% fishers used clean utensils for carrying fish to arat and 54.38% used uncleaned utensils. Average harvest per fishermen per day was 23.9 kg, of which 22.26 kg was sold in the market and 1.64 kg was used for own family consumption. Out of total fish landed, a 45.2% was transported by fish hold of the country boat, 21.9% by bamboo basket and 14.8% by plastic crate. Relatively small quantity of fish was transported by insulated ice box (4.7%), aluminum container (2.7%) and gunny bag (3.2%). A 32.6% fisherman used ice and 67.4 % fishermen did not use ice after harvesting of fish. During fishing season, fish and ice ratio used by the transporters was 2.62:1. The highest number of auctioneers were found in Chamra Ghat of Karimganj, while lowest were in Nikli, with an area of 55±1.44 and 25±8.42 decimal area per auctioneers being used for fish business. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (2), 75-88